Morphological and Molecular Characterisation of Ethanolic Neem (Azadirachta Indica) Leaf Extract In an in Vivo Breast Cancer Model - Lam, Tsuey Peng (2007)
Breast cancer is the commonest cause of cancer death in women worldwide and Malaysia in all ethnic groups and all age groups. Neem's (Azadirachta indica) ability as a medicinal herb is traced as far back as 4500 years ago. Some of the impressive therapeutic qualities have been discovered such as anti-viral, anti-microbial, anti-inflammatory, anti-tumour, anti-bacterial, anti-fungal and anti-hyperglycemic; however the anticancer effect of ethanolic Neem leaves extract against breast cancer has not been documented. Besides this, Neem was found to induce apotosis in MCF-7 breast cancer cell line in local study recently. Thus, this study was done to evaluate the effect of ethanolic Neem leaves extract as apoptosis inducer in in vivo 4Tl breast cancer model. Two different concentrations of Neem, 250 mgkg and 500 mglkg were tested on 4T1 breast cancer model. The 4T1 breast cancer models were evaluated by light microscopy, transmission electron microscopy for morphological changes, TUNEL assay for apoptotic cell labeling and in situ RT-PCR for c-myc, c-erbB2 and c-fos oncogene expressions. All treatment groups exhibited a higher incidence of apoptosis compared to untreated group from morphological analysis and TUNEL assay. The cancerous mice treated with both different concentration of Neem showed significantly higher value (p<0.05) in mean body weight, mean apoptotic index and mean apoptotic score compared to the control group. At the same time both group were showing a significantly lower value of mean mitotic index in histological evaluation. The mean tumour volume and mass proved that there was evidence of tumour regression in Neem treated mice. However, the overall observation showed that 500 mglkg of Neem has more significant effect (p <0.05) of inducing apoptosis in the 4T1 breast cancer cells compared to 250 mgkg of Neem. Furthermore, the 500 mgkg Neem concentration has significantly lengthened the mean survival time by 44.62% in the 4T1 breast cancer model (p <0.05). Neem 500 mglkg group also showed a better suppression of c-myc, c-erbB2 and c-fos oncogenes expression in mean distribution and intensity score (pc 0.05) in the 4T1 breast cancer model. By considering all the three down regulated oncogenes (c-myc, c-erbB2 and c-fos) under effect of Neem 500 mgkg together, it becomes clearer that Neem 500 mglkg was effective in inducing apoptosis in the 4T1 breast cancer model. In conclusion, the Neem 500 mglkg treatment was effective in inducing cell death via apoptosis and regulates cell proliferation in 4T1 breast cancer model. Its effectiveness was proportional to the concentration of Neem treatment given.